A Study on Wireless Mobile Phone Security Attacks and Secure Data Transfer - M, Inbavalli; V, Suriya (International Journal of Computer Sciences and Engineering, 2019)
Mobile phone becomes the foremost typical and fashionable mobile device in recent years. It combines the practicality of transportable and Personal Digital Assistant. Besides, it provides several computers’ practicality, like process, communication, knowledge storage and etc. But, some users may be permission to allow for device and application choices. Device to attack by victimization network. The common attacks for network to security attacks, privacy attack, region attack, Phishing Network Spoofing, Desktops, etc. How to secure the mobile data to secure and protected are Device Protection, Information Protection, Application Management Security, and manage the application permission. Transferring the data use the Encryption and Decryption methods. To avoid the problems should be used for responsible websites. This is worked for only server sides and secure or install firewall in your device. Mobile firewall is used to reduce the security risk and protect the integrity of the network device.